Pulsatile tinnitus due to vein of Labbé diverticulum and transverse sinus stenosis: a case report - Vences, Miguel Angel (2025)
Venous pulsatile tinnitus is an uncommon type of tinnitus caused by cerebral venous vascular etiology such as stenosis or venous thrombosis. We report the case of a 58-year-old male with pulsatile venous tinnitus with persistent symptoms despite symptomatic treatment and without defined etiology. The patient was referred to the interventional neuroradiology unit and underwent an angiography where stenosis in the left transverse sinus at the level of the vein of Labbé drainage was identified, along with a small diverticulum with slow flow. Based on the findings, endovascular stent placement was performed in the left transverse sinus. At the one-month follow-up the patient reported complete resolution of the tinnitus since the procedure was performed. Given that venous pulsatile tinnitus is associated with a decrease in quality of life and sometimes indicative of a serious vascular condition, an accurate diagnostic and therapeutic approach is crucial.